Advances on Sludge Properties and Dewaterability with Chemical Conditioning: A Review - Guan, Qinging; Zheng, Huaili; Tan, Mingzhuo; Tang, Xiaomin; Zheng, Xiaokai; Liao, Yi; Fan, Wei (Asian Journal of Chemistry, 2014)
Chemical conditioning of sludge dewatering has the advantages of simple operation, low investment cost and stable conditioning effect. It is the most commonly used pretreatment method. The components of sludge play an important role on sludge dewaterability and the choice of appropriate coagulants. The adoption of the coagulants contributes to the alteration of sludge characteristics and sludge dewaterability. The relationship between sludge components and chemical conditioning effects should be understood better to give lights to more appropriate selection of coagulants and the research of new coagulants. In this paper sludge properties including water distribution, sludge particle size distribution, the types and contents of metal ions and the fractions and structures of extracellular polymeric substances which would mostly affect sludge dewatering were reviewed as well as the chemical conditioning technologies and the methods' conditioning effects. Finally, the perspective of sludge properties research and chemical conditioning methods were discussed.